Long‐term survival in patients with metastatic gastric and gastroesophageal cancer treated with surgery. Issue 7 (14th April 2015) - Badgwell, Brian; Roy‐Chowdhuri, Sinchita; Chiang, Yi‐Ju; Matamoros, Aurelio; Blum, Mariela; Fournier, Keith; Mansfield, Paul; Ajani, Jaffer
Abstract : Background: The purpose of this study was to determine the survival of patients with metastatic gastric cancer treated with surgery. Methods: We reviewed the medical records of 7, 404 patients with gastric or gastroesophageal cancer seen from January 1995 to August 2012 at MD Anderson Cancer Center and identified patients with stage IV disease treated with surgery. Kaplan–Meier curves were created to compare overall survival (OS) between groups. Results: Of the 82 patients who met inclusion criteria, sites of metastatic disease included peritoneum (N = 34, 42%), positive cytology only (N = 17, 21%), distant lymph nodes (N = 12, 15%), and distant organs (N = 19, 23%). The median time from initial cancer diagnosis to surgery for metastatic disease was 10 months (range, 0–70). Surgery included exploratory surgery only (N = 16, 20%), primary tumor resection with or without resection of distant disease (N = 50, 61%), and distant disease resection only (N = 16, 20%). Median follow‐up for living patients was 3 years (range, 0.1–14). Median survival for all patients was 1.5 years (range, 0.1–14). Five year OS for patients with peritoneal metastases, positive cytology only, distant lymph nodes, and distant organ involvement was 13, 42, 20, and 34%, respectively. Conclusions: Surgery in the setting of metastatic disease is an uncommon clinical scenario and has a considerable risk of exploration without resection, although long‐term survival is possible. J. Surg. Oncol. 2015 111:875–881 . © 2014 Wiley Periodicals, Inc.